ANALYSIS OF COMMUNITY SATISFACTION ON TOURISM SERVICES INTEGRATED SERVICES (POSYANDU) IN LOMPO RIAJA KELURAHAN, TANETE RIAJA DISTRICT BARRU DISTRICT - Marsuki (Sean Institute, 2022)
The purpose of the study was to determine the level of community satisfaction with Posyandu Tourism Services in Lompo Riaja Village, Tanete Riaja District. This type of research used qualitative research, data collection techniques were carried out through observation, interviews and documentation. The results showed that Posyandu tourism was still in the socialization stage but was sufficient to give satisfaction to the people who visit the Posyandu activities every month, especially to mothers who have children under five, and mothers who are KB participants. still carried out at the district level, where toddlers get a certificate of proof that they have participated in Posyandu activities well. Factors that support community satisfaction with Posyandu Tourism Services are the presence of medical personnel from the Puskesmas, providing medical services, the presence of Posyandu cadres to organize activities, and guidance from the PKK Kelurahan Meanwhile, the inhibiting factor is the low awareness of residents participating in Posyandu activities, especially KB and EFA participants, the coaching funds are still lacking.